IMPACT OF THE LS-FACTOR ESTIMATION METHODS ON MEAN ANNUAL SOIL LOSS: Received: 8th November 2023 Revised: 04th December 2023, 26th December 2023, 02nd January 2023 Accepted: 15th November 2023 - Christopher Uche Ezeh; Kwasi Preko; Kwaku Adjei; Ogbonnaya Igwe; Sarah Schönbrodt-Stitt; Mensah Yaw Asare; Romanus Ayadiuno (LIFE: International Journal of Health and Life-Sciences, 2024)
Soil erosion was assessed in Anambra State using three different LS factor estimation methods. It showed that soil loss from the LS factor based on the slope in percent gives a good result with little underestimation with a PBIAS of -9.04 % while that based on slopes in radians performed best with a slight overestimation with a PBIAS of 2.81 %. The one based on degrees’ slope performed the least with a high underestimation with a PBIAS of -46.43 %. The result from field measurement yielded 27.76 t ha-1yr-1. The coefficient of variations was 241.47 %, 192.01 %, and 157.97 %, respectively, for slope in percent, radians and degree. Soil erosion is a highly variable phenomenon which was reflected by the high coefficient of variations. It shows that modelling soil erosion in the State with the LS factor estimation based on slopes in radians and percent yields better results. We believe this finding will be useful to authorities and scientists interested in soil erosion studies in the State. It is recommended that a similar study be extended to other terrains with moderate slopes.